Reverse Logistics: evaluation of potential and challenges in Santa Catarina Highlands (Brazil) - Goedert, Katynara; Oliveira, Larissa Roberta de Jesus; Salvador, Laura; Fagundes, Alexandre Borges; Beuren, Fernanda Hänsch; Vaz, Caroline Rodrigues (CONTRIBUCIONES A LAS CIENCIAS SOCIALES, 2025)
THIS IS AN ARTICLE PUBLISHED BY CONTRIBUCIONES A LAS CIENCIAS SOCIALES (e-ISSN: 1988-7833) ON 2025-03-25, AVAILABLE ONLINE: https://doi.org/10.55905/revconv.18n.3-276 Abstract This research analyzes the potential and challenges of implementing reverse logistics for batteries and electronic devices in the Santa Catarina Highlands (Brazil). Shared management in the region has been established through the Serra Catarinense Intermunicipal Consortium (CISAMA), which has set up ecopoints in various municipalities. These ecopoints aim to collect not only reverse logistics (RL) waste but also other recyclable materials. The Santa Catarina Environmental Institute (IMA), through the “I think, therefore I destiny” program, aims to make RL of this waste feasible in collaboration with local governments. In 2022, eleven municipalities in the mountainous region signed a cooperation agreement. The primary outcomes of this study, which utilized a SWOT matrix that considers the Santa Catarina Highlands as an internal environment and the state/country as external environments, revealed unique characteristics of the region. For example, many municipalities have populations of less than ten thousand residents, which presents obstacles such as a lack of professional qualifications among civil servants, the need for increased supervision, and the importance of raising public awareness. These issues encompass cultural, geographic, demographic, and administrative challenges.
Keywords: Reverse logistics; Batteries; Electronics; SWOT matrix; Santa Catarina Highlands